Predicting task performance and helping in multicultural teams : a skill-activation model of intercultural perspective taking. - Rockstuhl, Thomas. (2013)
In light of the continuing globalization of the workplace, the current study furthers our understanding of perspective taking in intercultural contexts and addresses two questions raised by Parker, Atkins, and Axtell (2008) about previous perspective taking research in organizational contexts. These questions concern a lack of understanding about a) the effects of perspective-taking skill, and b) contextual moderators of the relationships between perspective taking and outcomes.